Numerical assessment for aircraft cargo compartment fire suppression system safety - Xiong, Yifang; Diakostefanis, Michail; Dinesh, Akhil; Sampath, Suresh; Nikolaidis, Theoklis (Sage, 2021)
Fire on board an aircraft cargo compartment can lead to catastrophic consequences. Therefore, fire safety is one of the most important considerations during aircraft design and certification. Conventionally, Halon-based agents were used for fire suppression in such cases. However, an international agreement under the Montreal Protocol of 1994 banned further production of Halon and several other halocarbons considered harmful to the environment. There is therefore a requirement for new suppression agents, along with suitable system design and certification. This article aims to describe the creation of a mechanism to validate a preliminary design for fire suppression systems using Computational Fluid Dynamics and provide further guidance for fire suppression experiments in aircraft cargo compartments. Investigations were performed for the surface burning fire, one of the fire testing scenarios specified in the Minimum Performance Standard, using the numerical code Fire Dynamics Simulator. This study investigated the use and performance of nitrogen, a potential replacement for Halon 1301, as an environmentally friendly agent for cargo fire suppression. Benchmark fires using the pyrolysis model and fire design model were built for the surface-burning fire scenario. Compared with experiment results, the two Computational Fluid Dynamics models captured the suppression process with high accuracy and displayed similar temperature and gas concentration profiles. Fire consequences in response to system uncertainties were studied using fire curves with various fire growth rates. The results suggested that using nitrogen as a fire suppression agent could achieve a lower post-suppression temperature compared to a Halon 1301-based system. It can therefore be considered as a potential candidate for aircraft cargo fire suppression. Such work will feed directly into system safety assessments during the early design stages, where analyses must precede testing. Future work proposed for the application of this model can be extended to other fire scenarios such as buildings, shipping, and surface transport vehicles.
Keywords: Halon replacement; uncertainty study; fire suppression; performance analysis; Computational Fluid Dynamics modelling